Subjectivités et constructions sociales d’un risque iatrogène : (in)visibilités des lipodystrophies au Sénégal - Alice Desclaux; Sokhna Boye (Anthropologie & Santé)
Individual perceptions of the risk of drug-related adverse effects, whether anticipated before initiation of treatment or readjusted during treatment, are closely linked to social representations of damage. The ethnographic analysis conducted in Senegal on lipodystrophies due to certain antiretrovirals shows very different subjective perceptions, in a specific relationship to the social context. It also reveals a collective dynamic of invisibilisation based, on one hand, on a micro-social logic of avoidance of suffering in the absence of curative treatment and, on the other hand, on a symbolic logic of “price to pay” for the effectiveness of antiretrovirals. The model of patients’ “balancing” iatrogenic risk and efficacy seems relevant only if the drug is apprehended with its complex social inscription, using both concepts of “social life” and “political biography” of pharmaceuticals.